AGE AND GROWTH OF THE PHAETON DRAGONET, SYNCHIROPUS PHAETON (ACTINOPTERYGII: PERCIFORMES: CALLIONYMIDAE), FROM THE GULF OF ISKENDERUN, NORTH-EASTERN MEDITERRANEAN, TURKEY - Basusta, Asiye; Ozcan, Ebru, I; Basusta, Nuri (Wydawnictwo Akad Rolniczej W Szczecinie, 2020)
Background. Synchiropus phaeton (Gunther, 1861) is a sexually dimorphic, benthic species that inhabits mud bottoms. This fish is one of the important by catch species in the trawl fishing. There is no commercial value. But it has ecological importance in this area. The information about the biology of S. phaeton is very limited. This study was conducted to investigate the age and growth relation of phaeton dragonet inhabiting the Gulf of Iskenderun, north-eastern Mediterranean coast of Turkey. Materials and methods. A total of 289 phaeton dragonets were collected as discards during the commercial trawl fishing at the depth range of 100-150 m in the Gulf of Iskenderun, north-eastern Mediterranean. The fish age was determined from sagittal otoliths. The age readings were performed using Leica S8APO microscope and were documented with the Leica Application Suite (Ver. 4.8.0) software. The index of the mean percentage error (IMPE) was calculated to assess the precision of the age determination between two independent readers. Growth parameters for all specimens were subsequently determined by fitting the observed and the length-at-age data using the von Bertalanffy growth equations. Total length-weight relations (LWRs) and the condition factor (CF) were determined. Results. The total length and weight of S. phaeton ranged from 7.0 to 19.0 cm and from 2.01 to 22.0 g, respectively. The age of the studied individuals ranged from 2 to 7 years. The parameters of von Bertalanffy growth fitted to the mean observed total lengths-at age for each sex separately and were estimated as L-infinity = 23.358 cm, K= 0.248 year(-1), t(0) = -0.501 years for females and L-infinity= 26.543 cm, K= 0.156 year(-1), t(0) = -0.662 years for males, respectively. The overall growth performance index (G) value was determined as 3.46 for the combined sexes. The total length- weight relations were determined as W = 0.0121TL(2.55), R-2 = 0.94; 95% confidence intervals of b = 2.395-2.687, 1-test P < 0.05 for females and W = 0.0094TL(2.64),R-2 = 0.93; 95% confidence intervals of b = 2.470-2.803, 1-test P < 0.05 for males. The types of growth were found negatively allometric (b < 3). The highest condition factor was found at the age of 2 (0.62), while the lowest was found at the age of 6 (0.26). Conclusions. The presently reported study provides the first data on the age and growth of the S. phaeton that had not been studied previously in the Gulf of Iskenderun, north-eastern Mediterranean of Turkey. This study will contribute significantly to the conservation and management strategies of the species of S. phaeton in the future.
Keywords: Synchiropus phaeton; growth parameters; length-weight relations; sagittal otolith; condition factor